Arthur and the cootie-catcher - Krensky, Stephen (Brown, Marc Tolon. Marc Brown Arthur chapter book, 1999)
At Prunella's half-birthday party, her sister unveils a fortune-telling cootie catcher that seems to be able to predict the future.